Kartagener Syndrome: A Rare Genetic Disorder - Kunjan Shakya (Journal of Nepal Medical Association, 2009)
Kartagener Syndrome is a rare autosomal recessive disorder consisting of triad of sinusitis, bronchiectasis and situs inversus with dextrocardia. It is the subset of disorder called primary ciliary dyskinesia in which the cilia have abnormal structure and/or function resulting in multisystem diseases of various severity. Clinical manifestations include lifelong, chronic upper and lower respiratory tract diseases secondary to ineffective mucociliary clearance. Early diagnosis and management of chest infections can prevent irreversible damage to lungs and prevent potential lifelong complications. This case report is on a patient who presented with long standing history of sinusitis, bronchiectasis and on examination situs inversus with dextrocardia.